Controlling Algorithm for Energy-Consumption, Radio Bandwidth and Signal Strength Deploying Single Fitness Function to Solve Coverage Area Problems - Marsal, Kalid Abdlkader; Abdullah, Ismail; Waidah Ismail; Khairi Abdul Rahim (Amer Scientific Publishers, 2024)
Indexed by WOS/ Scopus